Cutting-edge technology application for prostate disease management in Indonesia: implementation of Healthcare 5.0 towards Indonesia’s Golden Vision 2045 - Hamid, Agus Rizal Ardy Hariandy (Faculty of Medicine Universitas Indonesia, 2024)
[No abstract available]